The announcement effect of bond and equity issues: evidence from Chile - Castillo, Augusto (Estudios de Economía, 2016)
This paper analyzes the impact of security offering announcements on stock prices for a sample of 172 issues of securities in the Chilean financial market, during the 1993-2002 period. We found that the authorization of bond issues given by the SVS (Superintendencia de Valores y Seguros) produced no significant abnormal returns, and that the authorization of equity issues given by the SVS produced a significant and negative abnormal return. We also found that the magnitude of the negative abnormal return was directly related to the relative size of the equity issue.